"To win back for Our Lady the flowers of the field": Ecology, Stewardship, and Prayer in the Mary's Gardens Apostolate - Groppe, Elizabeth Teresa (US catholic historian, 2025)
The Mary's Gardens apostolate was co-founded in 1951 by Edward A. G. McTague and John S. Stokes, Jr. It originated as a horticultural expression of the Marian ethos of mid-century U.S. Catholicism. At the same time, the apostolate was intended not only as an act of Marian devotion but also as a recovery of an entire worldview that approached nature as a witness to its Creator and Redeemer, inspiring the praise of God and virtuous living. The apostolate continued despite the waning of Marian devotions after Vatican II, and Mary Gardens remain part of the living tradition of Catholicism.